National Health Insurance Policy from the Perspective of Health Law and Human Rights Protection - Yulistiawati, Novitri; Lany, Arman (Research Horizon, 2025)
Indonesia’s national health insurance promises universal coverage, but its package-based tariffs and restricted drug list create tension with patient autonomy when individuals seek clinically superior treatments outside the formulary, generating a legal dilemma between patient rights and administrative limitations. This study aims to analyse the hierarchical position of these conflicting norms and determine the conditions under which voluntary cost-sharing is legally permissible. Using a normative juridical approach with statute and conceptual methods, the research examines the relationship between the Health Law and various implementing regulations on health insurance. The findings reveal that patient rights to complete information and autonomous decision-making hold superior legal status over financing limitations. Voluntary cost-sharing is lawful when based on transparent informed consent and separate written agreements that clearly distinguish guaranteed services from additional components chosen by patients. The study concludes that current restrictions represent limits on state subsidies rather than limits on clinical quality or patient freedom. Immediate revision of implementing regulations is recommended to explicitly recognise voluntary top-up mechanisms, accompanied by standardised transparency procedures in all health facilities to ensure legal certainty and protection for both patients and healthcare providers.